INTEGRASI ASPEK EKOLOGIS DAN EKONOMIS MELALUI KEGIATAN REFORESTASI DAN PENERAPAN SISTEM TANAM JAJAR LEGOWO DI NAGARI LUBUK KARAK, KABUPATEN DHARMASRAYA - Muhammad Parikesit Wisnubroto; Edwin Edwin; Wulan Kumala Sari; Sri Heriza; Dewi Rezki; Zahlul Ikhsan; Dede Suhendra; Nike Karjunita (LPPM Universitas Andalas, 2023)
Nagari Lubuk Karak is administratively located in the District of Nine Koto, Dharmasraya Regency, West Sumatra Province. Nagari is located in a sloping hill area with relatively good forest cover. However, today's environmental conditions in Nagari Lubuk Karak are constantly facing various threats that can damage the sustainability of the ecosystem, which are often caused by economic factors. This activity aims to provide education to the community in synergizing ecological and economic aspects so that the sustainability of the ecosystem in Nagari Lubuk Karak, which is in the upstream area, can always be maintained without compromising the community's welfare. This can be done by integrating reforestation activities using tree seeds that have economic value while at the same time intensifying rice cultivation owned by farmers by implementing the jajar legowo cropping system. This activity was carried out from 08 to 09 October 2022 in Nagari Lubuk Karak, Sembilan Koto District, Dharmasraya Regency. The implementation of the activity consisted of several stages, namely the socialization of reforestation activities and the application of the jajar legowo rice planting system, focus group discussions, and demonstrations of planting tree seedlings. The results of this activity can increase the knowledge and skills of the community regarding the importance of reforestation using tree seeds that have economic value while at the same time intensifying rice cultivation belonging to farmers by implementing the jajar legowo cropping system to increase farmers' income so that the economic and ecological aspects can work synergistically.